PENGARUH PENERAPAN PIJAT BAYI (BABY MASSAGE) TERHADP KUANTITAS TIDUR BAYI USIA 3 -12 BULAN DI PMB AFITA DELIANAH TUREN : Effect Of Implementation Of Baby Massage On Quantity Of Sleep In 3-12 Months Babies In Pmb Afita Delianah Turen - Yulia Tri Jayantj, Yulia; Sri Purwanti, Anik; Aksohini Wijayanti, Tut Rayani (LPPM - STIKES Pemkab Jombang, 2023)
Sleep quantity is a measure by which a person can easily initiate sleep and maintain sleep.Introduction: The effectiveness of baby massage on sleep quantity was influenced by increase in catecholamine hormone that trigger growth and development stimulations, increase appetite, increase body weight, increase sleep quality and quantity, and stimulate brain structure and function development. Objective of the research was to determinw effects of applying a baby massage to quantity of sleep for babies aged 3- 12 months at PMB Afita Delianah Turen. Methods: researcher applied one group pretest and posttest approaches. This research sample was 15 infants aged 3- 12month in accordance with inclusion criteria. In collecting technique applied SOP baby massage and observation sheets. Results: Using wilcoxson Analysis Test that acquiring significant values of 0. 000< (0. 05). Conclusion: There is effects of a baby massage application on sleep quantity of babies aged 3- 12months at PMB Afita Delianah Turen. It is recommended that mothers who have babies with sleep quantity disorders can be overcome with Baby Massage.